Green Investment in Contemporary Islamic Perspective: A Maqasid al-Syari‘ah Analysis of the Mining Industry in Morowali - Subli, Mohamad; Syamsuddin, Darussalam; Muhammad Amin, Abdul Rauf; Rahim, Wahida; Sulaiman, Sulaiman (MILRev: Metro Islamic Law Review, 2025)
This study aimed to analyze the implementation of the green investment paradigm in Morowali’s mining industry based on the principles of maqasid al-shari‘ah. The research method used was a qualitative approach with descriptive analysis through literature studies, interviews with mining industry stakeholders, and observations of the environmental impacts caused by mining activities. The data were analyzed using the maqasid al-shari‘ah approach to evaluate the extent to which the mining industry in Morowali had implemented sustainability principles in its operations. The results showed that although some companies had adopted environmentally friendly practices, such as land reclamation and the use of waste processing technologies, many aspects still did not align with maqasid al-shari‘ah. Excessive resource exploitation, environmental pollution, and social inequality remained, which impacted the welfare of the local community. In conclusion, the application of green investment in the mining industry of Morowali still required optimization based on maqasid al-shari‘ah, particularly in the areas of hifẓ al-bī’ah (environmental protection), hifẓ al-nafs (protection of life), and hifẓ al-māl (protection of wealth). Within the framework of contemporary Islam, this study emphasized the importance of revitalizing maqasid al-shari‘ah as an ethical and strategic foundation for sustainable investment. The academic contribution of this research lies in the integration of maqasid al-shari‘ah in the analysis of green investment in the mining sector, which has been limited in previous studies. This study provides a new perspective on Islamic economics by highlighting how the principles of maqasid al-shari‘ah can serve as an ethical framework for sustainable investment.